OUTSTANDING SPORTSMEN OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Abdumalikova Sevinch jasurbek qizi (TADQIQOTLAR.UZ, 2024)
ANNOTATION: This article explores the remarkable achievements and contributions of outstanding sportsmen from Uzbekistan across various disciplines. It highlights their impact on the global sports stage, their dedication to excellence, and the inspiration they provide to aspiring athletes. Through a detailed examination of their careers, accolades, and influence, this annotation sheds light on the significant role these sportsmen play in representing Uzbekistan on an international platform and shaping the country's sporting legacy.